Photo-identification of franciscanas (Pontoporia blainvillei) in Babitonga Bay, Santa Catarina State, Brazil - Sartori, C. M.; Paitach, R. L.; Cremer, M. J. (J. Cetacean Res. Manage., 2023)
The franciscana (Pontoporia blainvillei) is a small cetacean endemic to the South Atlantic distributed in coastal waters from Espírito Santo State in Brazil to Chubut Province in Argentina. Babitonga Bay, on the northern coast of Santa Catarina State, Brazil, is home to the only known franciscana population that resides throughout the year in an estuary. Photo-identification is a technique that serves to identify individuals in their natural environment through photographs of natural or artificial body marks. The objective of this paper was to assess the feasibility of identifying individuals from this population from marks present on the dorsal fin and the body. From February 2011 to August 2013, 172 boat surveys were carried out in Babitonga Bay. Groups of franciscanas were recorded on 576 occasions and on 542 of these (94.09%) were photographed. A total of 6,953 (11.89%) from a total of 58,471 photographs were considered of high enough quality to distinguish the features used to identify individuals. Throughout the sampling period, 23 franciscanas were identified. Most of the animals exhibited nicks on the trailing edge of the dorsal fin (82.6%), a mark of longterm duration. Scratches were recorded on only one animal on a single occasion. The rate of resightings ranged from 5.26% to 78.95%, with 39.13% of the individuals showing a rate higher than 50%. A total of 41.8% of the Babitonga Bay population was identified by the presence of marks on the dorsal fin. The study indicates that photo-identification can be applied to franciscanas, which may allow the realisation of various future studies. Because of this species threatened status, the use of this technique may become particularly important for monitoring franciscanas in Babitonga Bay and perhaps in other regions.